The Effect of System Quality Perceptions, Information Quality, and Service Quality on Accounting Information System Use and Satisfaction - Tera Aghny Sani; Negina Kencono Putri (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
This abstract should provide a brief introduction to the problem the effect of system quality, information quality and service quality on the use and user’s satisfaction of accounting information systems. The sampling technique used was accidental sampling with a sample size of 98 respondents who were BRI mobile banking users in Banjarnegara, Purbalingga, Banyumas, Cilacap and Kebumen (Barlingmascakeb). The data analysis method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of this study indicate that system quality and service quality have no effect on usage. Then the system quality and information quality have no effect on user’s satisfaction. Meanwhile, information quality and service quality have a positive effect on usage and user’s satisfaction.